Rhinitis and Related Upper Respiratory Conditions A Clinical Guide (Springer International Publishing, 2018)
This comprehensive book thoroughly covers the spectrum of rhinitis conditions and related comorbidities. Rhinitis and Related Upper Respiratory Conditions is a unique resource that delivers essential clinical information, addressing the varying patient populations which might be encountered in different types of clinical settings. Chapters range from topics such as pediatric, adult, geriatric, and occupational rhinitis, while also covering the full array of rhinitis subtypes and their complications. Later chapters address secondary causes of rhinitis such as systemic diseases manifesting as rhinitis, drug-induced rhinitis, and CSF leak. Written by experts in the field, every chapter is structured to contain clinical cases which illustrate the typical patient presentation, and their diagnostic work-up and treatment, providing the knowledge needed to further improve diagnosis and care for the patient with rhinitis. Rhinitis and Related Upper Respiratory Conditions is an ideal resource for allergists, primary care physicians, and health care extenders, to help them recognize and further improve care of patients with rhinitis.